2017
DOI: 10.3389/fcimb.2017.00176
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutrophils Produce CCL23 in Response to Various TLR-Agonists and TNFα

Abstract: CCL23, also known as myeloid progenitor inhibitory factor (MPIF)-1, macrophage inflammatory protein (MIP)-3, or CKβ8, is a member of the CC chemokine subfamily exerting its effects via CCR1 binding. By doing so, CCL23 selectively recruits resting T lymphocytes and monocytes, inhibits proliferation of myeloid progenitor cells and promotes angiogenesis. Previously, we and other groups have reported that human neutrophils are able to produce chemokines upon appropriate activation, including CCR1-binding CCL2, CCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…Another example of the differential cytokine expression between human neutrophils and monocytes concerns CCL23, which is a chemokine that binds to CCR1 and thus exerts chemotactic activities on monocytes, DCs and resting T lymphocytes. We found that while neutrophils and monocytes produce similar levels of CCL23 in response to R848, only monocytes, but not neutrophils, manufacture CCL23 upon incubation with IL‐4 . Under the latter experimental conditions, however, neutrophils promptly accumulate IL‐1ra mRNA, indicating that they do respond to IL‐4.…”
Section: Molecular Mechanisms Controlling Cytokine Expression In Humamentioning
confidence: 72%
See 3 more Smart Citations
“…Another example of the differential cytokine expression between human neutrophils and monocytes concerns CCL23, which is a chemokine that binds to CCR1 and thus exerts chemotactic activities on monocytes, DCs and resting T lymphocytes. We found that while neutrophils and monocytes produce similar levels of CCL23 in response to R848, only monocytes, but not neutrophils, manufacture CCL23 upon incubation with IL‐4 . Under the latter experimental conditions, however, neutrophils promptly accumulate IL‐1ra mRNA, indicating that they do respond to IL‐4.…”
Section: Molecular Mechanisms Controlling Cytokine Expression In Humamentioning
confidence: 72%
“…Human neutrophils have been shown to express and produce either in vitro or in vivo, particularly upon appropriate stimulation, many pro‐ and anti‐inflammatory cytokines (including TNFα, IL‐1β, IL‐1ra, IL‐6), chemokines (including CXCL1, CXCL8, CXCL10, CCL2, CCL3, CCL4 and, as more recently described, CCL23), colony‐stimulating and angiogenic factors (including G‐CSF and VEGF), TNF family members (including TRAIL, FasL and BAFF) and growth factors (HB‐EGF) (Figure ). These findings, in the face of multifold evidence are making it clear that neutrophils are functionally involved in a variety of physiological and/or pathological processes, such as hematopoiesis, angiogenesis, wound healing, autoimmune and neoplastic diseases, obviously in addition to acute inflammatory diseases.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…We recently identified R848 and CL075 as very powerful agonists able to trigger a remarkable extracellular production of cytokines, including TNF‐α, IL‐6, G‐CSF, and CCL23 . R848 and CL075 are synthetic compounds that in human neutrophils specifically act via TLR8, because TLR7, their other receptor, is absent and not inducible following cell activation .…”
Section: Introductionmentioning
confidence: 99%